Educational Games Let's Learn Japanese Using The Unity 3d Based Android: Educational Games Let's Learn Japanese Using The Unity 3d Based Android - Alfian Cutryanto; Fauziah Fauziah; Ratih Titi Komala Sari (Jurnal Mantik, 2020)
Japanese is the language most popular and studied by students. Although it is popular with many people who find it difficult to learn Japanese because of its complicated writing and grammar it is much different from Indonesian. One of the media that helps beginners learn about it is learning Japanese in educational games. This research aims to make it easier for beginner learners to learn Japanese, so that users do not get bored with learning methods in class and help learning become more enjoyable. The research method used is research and development. with the ADDIE model (Analysis, Design, Development, Implementation and Evaluations). And using Unity 3D was chosen because of its ability to create more interesting animations and easier to use.